2001
DOI: 10.1074/jbc.m007520200
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of Cell-specific MAP Kinase Control of the Tryptophan Hydroxylase Promoter

Abstract: The neurotransmitter serotonin controls a wide range of biological systems, including its own synthesis and release. As the rate-limiting enzyme in serotonin biosynthesis, tryptophan hydroxylase (TPH) is a potential target for this autoregulation. Using the serotonergic neuron-like CA77 cell line, we have demonstrated that treatment with a 5-hydroxytryptamine autoreceptor agonist, CGS 12066A, can lower TPH mRNA levels and promoter activity. We reasoned that this repression might involve inhibition of MAP kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
(68 reference statements)
2
25
0
1
Order By: Relevance
“…Although MEKK potentiates D2R promoter activity, MEKK acts as an upstream kinase of the three major MAPKs: ERK, JNK and p38MAPK (Wood et al 2001). To determine which MAPK is involved in potentiation of D2R promoter activity, we examined effects of both selective MAPK inhibitors and dominant negative mutants of JNK1 and p38MAPK on MEKK-induced potentiation in NB2A cells.…”
Section: Inhibition Of Mekk-induced D2r Promoter Activity By U0126mentioning
confidence: 99%
See 1 more Smart Citation
“…Although MEKK potentiates D2R promoter activity, MEKK acts as an upstream kinase of the three major MAPKs: ERK, JNK and p38MAPK (Wood et al 2001). To determine which MAPK is involved in potentiation of D2R promoter activity, we examined effects of both selective MAPK inhibitors and dominant negative mutants of JNK1 and p38MAPK on MEKK-induced potentiation in NB2A cells.…”
Section: Inhibition Of Mekk-induced D2r Promoter Activity By U0126mentioning
confidence: 99%
“…To evaluate the effects of these pathways, we expressed constitutively active mutants of MEKK, PKA, CaMKII and CaMKIV. MEKK acts as an upstream kinase of three major MAPKs: extracellular signalregulated kinase (ERK), c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (p38MAPK) (Wood and Russo 2001). These MAPKs phosphorylate transcription factors such as Elk-1, c-Myc, c-Jun and c-Fos and regulate their transcriptional activities (Davis 1995;Fukunaga and Miyamoto 1998;Curtis and Finkbeiner 1999).…”
mentioning
confidence: 99%
“…The T153A and T153E mutant USF1 vectors were generated from the USF1 vector using the QuikChange site-directed mutagenesis kit (Stratagene). The MEKK (amino acids 380 -672) plasmid from Stratagene has been described (30).…”
Section: Methodsmentioning
confidence: 99%
“…We then tested the effect of USF and MAP kinase activation in the NCI-H460 lung carcinoma cell line because these cells are known to have a low level of endogenous USF1 and USF2 proteins (36). Separate overexpression of USF2 or the upstream activator of the ERK MAP kinase, MEK1 (30), increased CGRP promoter activity by 5-fold. In contrast, combined overexpression of USF2 and MEK1 yielded a synergistic 20-fold increase in promoter activity (Fig.…”
Section: Map Kinase Regulation Of Usf In Trigeminal Ganglia Cultures-mentioning
confidence: 99%
“…Recently it has been demonstrated that activation of ERK in the RVM also contributes to persistent neuropathic pain (Geranton et al, 2010). Under the special condition of chronic restraint stress, persistent ERK activation induced by chronic stress may increase the transcription of tryptophan hydroxylase (TPH), a rate-limiting enzyme in serotonin biosynthesis (Wood & Russo, 2001), leading to central sensitization of dorsal horn neurons via descending serotonergic facilitatory projection (Fig. 9).…”
Section: Descending Facilitation In Chronic Stress and Chronic Pain Smentioning
confidence: 99%